A City Reborn: The Transfiguration of Seoul into a Paragon Metropolis - Vismaya Vinod Nair; Gaddam Shravanthi (International Journal of Architectural Design and Planning, 2024)
Seoul the capital of South Korea is a megacity with a population of 10 million people and an area of 605 square kilometres. It has a long history and cultural legacy, dating back over 600 years. Examining and understanding the urban morphology right from Joseon to the early 20th century. During the Japanese occupation and the Korean War, Seoul's identity and form were badly harmed. In 1970 the city swiftly recovered and thrived, focusing on relocating its key operations and people to the city's outskirts. This was due to the overcrowding in the city center. The city focused on its urban structures, which are made up of blocks, plots, and the street network, as well as its City Beautiful initiative. The 2030 Seoul blueprint is the highest legislative blueprint for urban expansion. Seoul recently created a 100-year Urban Planning Framework. In order to promote resident involvement and solve specific community issues, neighbourhood plans have been put into place. The city's urban planning initiatives aim to preserve its historic heritage while creating a sustainable and liveable environment. The morphological development of Seoul is examined in this study from the Palaeolithic era to the present urban proposal for urban improvement in the context of river rehabilitation, public transportation and historical preservation.
Keywords: City; blocks; city beautiful movement; development; economy; infrastructure; neighbourhood; policies; solutions; strategies; street networks; sustainable; sustainable environment; technology; urbanization